Role of S100A9 in the comorbidity asthma and acute pneumonia - Boko, Mèdéton Mahoussi Michaël (2023)
Pneumonia caused by Streptococcus pneumoniae can improve or exacerbate asthma. The exacerbation of asthma and pneumonia comorbidity may be due to the induction of neutrophilic inflammation, which is characterized as more severe asthma and difficult-to-treat. S100A9 is an alarmin that acts as an endogenous danger signal and promotes neutrophil recruitment. This alarmin is involved in the immunopathology of different diseases that affect the lungs, such as asthma and pneumonia. We hypothesize that acute pneumonia induced by S. pneumoniae exacerbates lung inflammation in asthma through the induction of S100A9, which contributes to neutrophilic inflammation and the production of Neutrophil Extracellular Traps (NET). C57BL/6 Wild Type (WT) animals and mice deficient for the expression of S100A9 (S100A9-/-) were sensitized and challenged with ovalbumin (OVA) and infected or not with S. pneumoniae during the challenge. In WT mice, pneumococcal infection concomitant with allergen exposure resulted in a significant increase in neutrophil recruitment in the bronchoalveolar lavage fluid (BALF), accompanied by increased perivascular and peribronchial leukocyte infiltrate, S100A9 secretion, and NET production in the lungs compared to WT mice exposed only to the allergen. During the comorbidity, S100A9 deficient mice exhibited a significant reduction in the concentrations of CXCL1, a chemokine that attracts neutrophils, and in BALF neutrophil influx. Furthermore, during the comorbidity, S100A9 deficient mice showed increased neutrophil death. Pharmacological intervention with tasquinimod or azeliragon, inhibitors of S100A9 signaling, or BB Cl-amidine, a NET inhibitor, protected mice from neutrophilic inflammation and NET production during the comorbidity of asthma and acute pneumonia. Our results provided evidence that S100A9 and NET can be therapeutic targets in severe asthma that course with neutrophilic inflammation resulting from pneumonia.